URGENSITAS PEMBENTUKAN LEMBAGA PENYELENGGARAAN PELINDUNGAN DATA PRIBADI - Rizky Pratama; Evi Retno Wulan (Gapenas Publisher, 2023)
Indonesia has experienced several data leaks in cyberspace. The government passed Law No.27 of 2022 on Personal Data Protection as an effort to overcome this. In this law, the government will establish an institution that organizes the protection of personal data. The purpose of this study is to immediately establish a presidential regulation to regulate in detail the form of the Supervisory Institution for Personal Data Protection so that it can carry out its duties and authorities optimally. The research method used in this research is qualitative method. This research uses normative legal research or called doctrinal legal research. The approaches used are statute approach, conceptual approach, and comparative approach. (comparative approach). The results of this study explain that broadly speaking, the establishment of personal data protection organizers is an answer to the needs of the community to obtain personal data protection. personal data protection organizers can also be utilized by the community to complain or channel their aspirations related to personal data protection. Therefore, the ideal institution is independent